Rethinking the relationship in the family according to Foucault - Adriane Maria Netto de Oliveira; Rosane Gonçalves Nitschke; Mara Regina Santos da Silva; Giovana Calcagno Gomes; Josefine Busanello (Rev Rene)
The aim of this study is to reflect on family relationships taking into account the ideas of Foucault. As we think about such relationships, it is important to consider the potential and limitations of its members in order to propose interventions that could promote family health. It brings considerations about the emotional bond, marital relations of power in the family context and relationships in the family as possibilities of “being”. We may conclude that one of the roles of health professionals is to encourage the subjects to verbalize their difficulties, their emotions, their needs and find out about their potential in order to build a more harmonious coexistence and have a healthier family relationship.